2002
DOI: 10.1111/j.1574-695x.2002.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofvacAgenotypes inHelicobacter pyloristrains isolated from Brazilian adult patients with gastritis, duodenal ulcer or gastric carcinoma

Abstract: This PCR-based analysis is the first molecular epidemiological study in Brazil testing Helicobacter pylori cagA and vacA distribution in adults with gastric complaints, that includes a large number of carcinoma patients. Multiple-strain infection was identified in 11/13.4% patients. vacA s1-m1 and cagA(+) genotypes were the most common in patients with a non-mixed infection. All vacA s1 strains were s1b, so subtyping s1 strains was not useful. vacA s1b-m1 and cagA(+) strains were associated with higher prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…As reported by [42,43] iceA1 expression is associated with a higher activity of the gastric inflammation, a condition that increases the risk for developing ulcer disease and gastric carcinoma.…”
Section: Discussionmentioning
confidence: 75%
“…As reported by [42,43] iceA1 expression is associated with a higher activity of the gastric inflammation, a condition that increases the risk for developing ulcer disease and gastric carcinoma.…”
Section: Discussionmentioning
confidence: 75%
“…Cytotoxin associated gene A (CagA) is the most important pathogenic factor of H. pylori and plays a crucial role in the occurrence of gastric cancer [13]. Earlier studies by other groups have reported that CagA-positive H. pylori strains were isolated from almost all patients with gastric cancer [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The vac A is a polymorphic gene with two main signal region genotypes s1 and s2, and two different alleles in the mid region of the gene named m1 and m2. Infection with strains possessing the s1m1 genotype has been associated with precancerous gastric hypochlorhydria [17] and gastric carcinoma [19]. …”
Section: Introductionmentioning
confidence: 99%